Determination of the complex refractive index of compound semiconductor alloys for optical device modelling. (2nd October 2020) - Schygulla, Patrick; Fuß-Kailuweit, Peter; Höhn, Oliver; Dimroth, Frank
Abstract: In this paper a method is presented to accurately and quickly interpolate a dataset of the complex refractive index of arbitrary compound semiconductors. The method is based on a parameter morphing algorithm which maps critical points of two endpoint materials with known optical parameter sets onto each other. Every desired intermediate material composition can be interpolated if the composition dependence of the band gap is known for the given material system. The accuracy and stability of the proposed procedure is validated experimentally using spectral ellipsometry and reflection measurements. Test samples of two III–V semiconductor material systems, AlGaAs and GaInAsP, with various compositions were grown using metalorganic vapour phase epitaxy and the morphed parameter sets are compared to corresponding measurement results. Modelling the absorption of a solar cell device and comparing it to the external quantum efficiency is presented as an application example of this method. The interpolation method is demonstrated to be a powerful tool for optical and electro-optical modelling of semiconductor structures if parameters of the complex refractive index are not available for the exact material composition.